Substance use disorders during the COVID-19 pandemic: looking for new innovative approaches - Piersanti, Valeria; Consalvo, Francesca; Marinelli, Enrico (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The destructive impact of the still ongoing COVID-19 pandemic on those struggling with substance use disorders (SUD) stems from the daunting challenges which SUD patients experience in terms of coping with their condition and receiving care in a timely fashion. Methods: Patients struggling with addiction are at particularly high risk, due to the underlying vulnerabilities in their conditions and the stigmatization they often suffer. New Psychoactive Substances stand out as a critical area of concern. The authors have conducted a broad-ranging search to assess the impact of SUDs, along with their related mental, physical, and behavioral symptoms, against the backdrop of the COVID-19, taking into account how drug trafficking and consumption trends have evolved as the emergency draws out, and the cyberspace comes to play an ever-bigger role. Results: Given that roughly 1.5%-5% of the global burden of disease can be ascribed to alcohol abuse and substance addiction, the role of pandemic-related potential contributing factors in the exacerbation and relapse of SUDs and behavioral addiction cannot be discounted and needs targeted measures tailored to the special needs of SUD patients. Escalating environmental stressors stemming from abnormal circumstances can undermine recovery efforts and threaten the very survival of countless SUD patients, increasing the likelihood of relapsing for those in recovery. Conclusions: Policymakers and legislators have not yet put in place targeted measures and adjustments in the health care delivery mechanisms in order to countervail the pandemic impact on SUD sufferers, and the ever-evolving patterns of use and trafficking.